# How do you simplify #(sqrt49(a^2)(b^-8))#?

##### 1 Answer

Oct 12, 2015

#### Answer:

#### Explanation:

Your starting expression looks like this

#sqrt(49) * a^2 * b^(-8)#

The first thing to notice here is that *perfect square*, which means that you can write

#49 = 7 * 7 = 7^2#

#sqrt(49) = sqrt(7^2) = 7#

The expression becomes

#7 * a^2 * b^(-8)#

Next, rewrite the negative exponent by using

#x^(-n) = 1/x^n" "# , for#x!=0#

In your case, you have

#b^(-8) = 1/b^8#

The expression will thus be

#sqrt(49) * a^2 * b^(-8) = color(green)(7 * a^2 * 1/b^8)#